Modern Anthropogenic Hydrosphere of Ukraine - Denysyk, H. I.; Yatsentiuk, Yu. V.; Denysyk, B. H.; Chyzh, O. P.; Voina, I. M. (Ukrainian Geographical Journal, 2024)
The purpose of the research is to analyze the formation and current state of the anthropogenic hydrosphere of Ukraine with a view to its rational use. Utilized methods include field research, literary-cartographic, collecting and processing statistical information, theoretical generalization and systematization of facts, and GIS technologies. It is shown that active anthropogenization from the Upper Palaeolithic until now has led to the replacement of the natural hydrosphere of Ukraine by the anthropogenic one. Various types of soil melioration and the formation of irrigation, drainage, and irrigation-drainage systems facilitated this process. The construction of numerous reservoirs (1,054) and ponds (49,440), derived reservoirs, and surface and underground water objects added to the problem. The processes of anthropogenization of the natural hydrosphere of Ukraine are examined in more detail, drawing on the example of small (the Silnytsia), medium-sized (the Trubizh), and large (the Pivdennyi Buh and the Dnipro) rivers. It was noted that overloading reservoirs, ponds, and melioration systems of most small and medium-sized rivers have completely lost their natural properties and features. In part, this also applies to large rivers, particularly the Dnipro. Only a 30–40 km long section of the river and its floodplains retained their natural state. Reservoirs account for the rest of its sections. They form an aqua-marsh area with Europe’s largest complex of hydraulic engineering structures. Despite this, landscape scientists and hydrologists continue to study rivers, reservoirs, ponds and, in part, canals individually. The novelty of the research consists of revealing the spatial-temporal features of the transformation of the natural hydrosphere of Ukraine into an anthropogenic one, as well as a thorough analysis of its current state.